دراسة الامتيازات الجبائية والشبه جبائية للمقاول الذاتي حسب قانون 22-23 بالجزائر - بوعكاز ،يوسف; حاجي، منال (جامعة الوادي University of Eloued, 2024)
تهدف الدراسة إلى تسليط الضوء على الامتيازات الضريبية والشبه ضريبية الممنوحة للمقاولين الذاتيّين وفقا للقانون 22-23 في الجزائر، حيث اعتمدت الدراسة على تحليل الإطار المفاهيمي وحقوق والتزامات المقاول الذاتي في جانبها النظري، بينما تناولت في الجانب التطبيقي تأثير الامتيازات الجبائية والشبه جبائية على مقاول ذاتي يمارس نشاط إنجاز المواد الإعلامية. توصلت الدراسة إلى نتائج مهمة منها أن القوانين الجزائرية تشجع أصحاب المشاريع الصغيرة على التسجيل في السجل الوطني للمقاول الذاتي، مما يعزز ممارستهم لنشاطاتهم بشكل قانوني عبر فتح حسابات بنكية والفوترة، هذه الامتيازات ومن خلال فرض معدلات ضرائب مخفضة مقارنة بحجم الأعمال تساهم في إزالة العوائق أمام رواد الأعمال الجدد وتجنب التهرب الضريبي، مما يعزز الاقتصاد الوطني. The study aims to highlight the tax and para-tax advantages granted to self-employed entrepreneurs under Law 22-23 in Algeria, the study relied on analyzing the conceptual framework and the rights and obligations of the self-employed in its theoretical aspect, while the practical side examined the impact of tax and para-tax advantages on a self-employed entrepreneur engaged in producing media materials. The study reached important conclusions, including that Algerian laws encourage small business owners to register in the national self-employed register, which enhances their ability to conduct their activities legally through opening bank accounts and invoicing, these advantages through the application of reduced tax rates compared to the volume of business, contribute to removing obstacles for new entrepreneurs and avoiding tax evasion, thereby strengthening the national economy.
Study of Tax and Para-Tax Advantages for Self-Employed Entrepreneurs According to Law 22-23 in Algeria: An Empirical Study of a Self-Employed Entrepreneur in 2024
Keywords: مقاول ذاتي; امتيازات جبائية; امتيازات شبه جبائية; الضريبة الجزافية الوحيدة; الجزائر; Self-employed; tax advantages; para-tax advantages; Algeria.